ANALISIS KEBERLANJUTAN PENGHIDUPAN DAN USAHA PETERNAKAN KAMBING DAN DOMBA DI KABUPATEN TULUNGAGUNG - Hana Nur Eritrina; Joko Gagung Sunaryono (Universitas Tribhuwana Tunggadewi, 2025)
Goat and sheep farming in Tulungagung Regency plays a crucial role in rural livelihoods, yet it still faces economic vulnerability, institutional limitations, and environmental pressures. Furthermore, studies on sustainability, which link livelihood assets to business performance at the local level, are still limited. This study aims to assess the level of livelihood and business sustainability among farmers and identify key livelihood assets that influence business resilience. Data were collected from 73 farmers through structured questionnaires and analysed using an ordinal scoring method (1–3) for 14 indicators grouped into five livelihood assets and three dimensions of sustainability (economic, social, and environmental). The results show that 49.32% of farmers have achieved the sustainable livelihood category, while 54.79% of businesses remain in the moderately sustainable category. The environmental dimension shows the best performance, and the economic dimension is the weakest, due to low income, limited access to capital, and price fluctuations. The main obstacles faced include livestock diseases, limited feed, and lack of institutional support. It can therefore be concluded that the sustainability of goat and sheep farming businesses in Tulungagung is still relatively fragile and requires strengthening in economic and institutional aspects, particularly through increased access to capital, feed provision, and strengthening of marketing institutions.